Voluntary Exile and Eisangelia in Athens: Remarks about the Lawfulness of a Widespread Practice (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2020)
This paper aims to investigate the question of the (un)lawfulness of voluntary exile by defendants in relation to eisangelia trials. I argue that the defendant’s habit of evading trial by going into exile was never seen as lawful, despite the frequency with which it occurred. First, I examine the issue of alternating between the death penalty and exile in eisangelia trials with the aim of showing that exile was not a penalty linked to the procedure of impeachment. Then, I argue that Athenian law took into consideration the issue of the (un)lawfulness of self-exile, as demonstrated by the existence of an Athenian law concerning the same matter in homicide cases. Lastly, I analyse some ancient passages that allow us to state that defendants in high treason trials who evaded justice were likened to outlaws. Elements such as the practice of setting bounties on those who escaped trial, extradition requests for fugitives, the imposition of additional penalties such as confiscation of property and inscribing the fugitive’s name on a bronze stele, can corroborate this assumption.